Respuesta :

Answer:

Step-by-step explanation:

15. (-4-3)/(-5-0)= -7/-5= 7/5

      y - 3 = 7/5x - 0

      y = 7/5x + 3

16. (-2-3)/(4-0)= -5/4

     y - 3 = -5/4x - 0

     y = -5/4x + 3

17. (-3+5)/(0+3)= 2/3

    y + 5 = 2/3(x + 3)

     y + 5 = 2/3x + 2

     y = 2/3x - 3

18. (-2-2)/(0+4)= -4/4= -1

       y - 2 = -1(x + 4)

       y - 2 = -x - 4

       y = -x - 2

19. y - 3 = 1/2x - 0

     y = 1/2x + 3

20. y - 2 = -(x + 1)

      y - 2 = -x - 1

      y = -x + 1

21. perp. -5/3

y + 5 = -5/3x  + 0

 y = -5/3x - 5

22. perp. 1/2

   y + 1 = 1/2(x + 4)

   y + 1 = 1/2x + 2

   y = 1/2x + 1

23. perp. 3/4

   y + 5 = 3/4(x + 4)

   y + 5 = 3/4x + 3

   y = 3/4x - 2

24. perp. 7/5

 y - 4 = 7/5(x - 5)

 y - 4 = 7/5x - 7

 y = 7/5x - 3